Psychosocial risks of healthcare professionals and occupational suicide. Issue 1 (12th November 2019) - Sullivan, Shantel; Germain, Marie-Line
Abstract : Purpose: The purpose of this paper is to explore compassion fatigue and psychosocial risks among healthcare professionals, which lead to increased work-related costs, including occupational suicide. Through this review and synthesis of the literature, the authors shed light on the causes that lead medical professionals to take their own lives. In addition, the authors explore the role of compassion fatigue as a leading cause of self-inflicted death. Design/methodology/approach: A systematic approach was used to guide the review and synthesis of the literature. Key bibliographic and review databases were searched from the fields of social work, nursing, medical education, educational leadership, psychology, sociology and human resources. Findings: In the USA alone, suicide has increased by 25 per cent since 1999, making it a leading cause of death. Data indicate that medical professionals are prone to compassion fatigue, work-related stresses and suicide at a greater rate than the general population, with surgeons reporting up to three times more thoughts of suicide than the general population. The synthesis and analysis of the literature yielded the following themes: compassion fatigue and suicides, burnout and compassion fatigue, career longevity and moral distress. Research limitations/implications: Job stress and its negative impact on the workforce is rather well documented. Yet, job stress has shown to be a leading cause of workplace suicide, which represents a commensurable human and economic loss and has a direct impact on multiple human resources variables. Ongoing research is needed to see how the initial literature has evolved as new data emerges. Practical implications: This paper presents best practices for training and development professionals to better respond to psychosocial risks and reduce work-related costs in the medical profession and beyond. Originality/value: Studies on employee stress and suicide in the healthcare industry are scarce. Yet, they have human and economic impacts on organisations.